유아기부터 청소년기까지 집행기능의 측정에서의 문제 고찰: 스트룹 효과를 중심으로 - 이새별; Saebyul Lee (영유아아동정신건강연구, 2023)
집행기능이 개인의 적응과 발달에 미치는 중요성이 널리 알려져 있고, 많은 연구결과가 보고되고 있음에도 불구하고, 발달궤적이나 변화의 기저과정에 대한 이해가 매우 부족하다. 이는 다양한 연령집단에서 유사하나 서로 다른 행동과제를 통해 집행기능을 측정하는 현재의 연구경향과 일정부분 관련되어 있다는 점을 간과할 수 없다. 본 연구는 집행기능이라는 구성개념이 아니라 이를 측정하기 위해 가장 많이 사용되고 있는 스트룹 혹은 유사 스트룹 패러다임을 활용한 연구들을 발달적 관점에서 조직하고 개관하여, 다양한 연령집단에서 사용되는 측정의 양상과 관련된 문제점 그리고 결과에서 드러난 발달적 변화의 해석의 타당성에 대해 논의하였다. 구체적으로, 다양한 형태의 스트룹 과제에서 보고되는 촉진 및 간섭효과가 동일한 원인에서 발생하는 것이 아니며, 억제통제능력 역시 연령집단에 따라 서로 다른 양상으로 측정됨을 확인하였다. 따라서, 다양한 연령 집단에서의 집행기능의 발달양상을 확인하고 기저 메커니즘을 이해하기 위해서는 단순한 동일한 형태의 과제를 사용하는 것을 넘어, 각 연령집단의 지식수준과 관련한 지각 및 인지능력을 고려하여 관찰된 수행결과를 해석하는 것이 필수적이라고 제안한다. Despite numerous research findings on executive functions in children, there remains a significant gap in our understanding of the developmental trajectories and underlying mechanisms of these functions. This gap can be partly attributed to the prevailing research approach, which assesses executive functions through various behavioral tasks exhibiting both similarities and differences in their measurement of executive functions. This article organizes and reviews research that utilizes the Stroop paradigm or similar tasks, which are the most commonly employed methods for measuring executive functions, from a developmental perspective. The review addresses the issues concerning measurement patterns across various age groups and questions the validity of interpreting developmental differences in the results. Notably, the review presents that the facilitation and interference effects in various Stroop tasks do not originate from the same underlying causes, and the measurement of inhibitory control abilities can vary across different age groups. Asﾠa result, this article underscores the importance of moving beyond the use of identical task forms and emphasizes the need to consider the perceptual and cognitive abilities associated with the knowledge levels of each age group when interpreting observed performance outcomes to comprehend the developmental patterns and underlying mechanisms of executive functions across diverse age groups.